Análise de marcadores moleculares como potenciais preditores de malignidade em tumores epiteliais da tireoide - GASPAR, Silvia Antonia Sá (2021)
Introduction: Thyroid cancer (CT) is the most frequent endocrine neoplasm worldwide and its incidence has been growing significantly in the last three decades, currently representing about 1% of all malignancies. The most common cause of papillary thyroid carcinoma (PTC) is a single mutation in the BRAF gene, present in 51% of cases, depending on age and histological subtype. OBJECTIVE: To evaluate the main genetic alterations in members of the MAPK and telomerase activation pathways in patients with thyroid tumors of different histological types in Maranhão. METHODOLOGY: We analyzed 112 surgical specimens obtained from patients undergoing thyroidectomy at Hospital do Cancro Aldenora Bello (HCAB) between 2018 and 2021. Genomic DNA was extracted from fresh tissue and subsequently performed by real-time PCR to assess the BRAFV600E variant and DNA sequencing (Sanger) to investigate alterations in NRAS (codon 61) and the TERT promoter region (positions C228T and C250T). RESULTS: The presence of the BRAFV600E variant was detected in 60 of 112 patients evaluated (53.5%). All genetic alterations were observed in patients with histopathological diagnosis of TLC, with the classic variant being the most abundant. Regarding NRAS gene analysis, the presence of the CAA>CGA(Q61R) variant was detected in 5 of 89 patients studied (5.6%). For the TERT gene analysis, the presence of the C228T alteration was identified in 3 of the 89 patients studied (3.4%). In addition, the occurrence of variants in TERT and BRAF was also observed in 2 of the patients studied. In this study, associations were observed between BRAFV600E and recurrence risk factors, such as TSE and high FNAB grade, and TERT gene C228T with tumor size and recurrence risk. CONCLUSION: The frequencies of gene mutations in the study population are in agreement with what is described in the literature. The presence of BRAFV600E mutation was observed exclusively in CPT with predominance in the classic variant. The coexistence of BRAF and TERT alterations seems to indicate a worse prognosis.